Ertapenem Susceptibility of Extended Spectrum Beta-Lactamase Producing E Coli and K Pneumoniae - Shah, Kinal; Shrimali, Gaurishanker; Mulla, Summaiya (National Journal of Community Medicine, 2016)
Background: Multidrug resistant organism such as extended spectrum beta-lactamase (ESBL) – producing E. coli and K. pneumoniae are increasing in critical ill patients. Carbapenem [Imipenem and Meropenem] are the antibiotics of choice to treat them. Ertapenem, newest Carbapenem has limited clinical data regarding its efficacy against these organisms. Objectives: Objective of study is to compare susceptibility of ertapenem to imipenem and organisms are susceptibility of ertapenem to imipenem could be used as a surrogate for ertapenem susceptibility. Materials and Methods: 53 ESBL isolates (n==26 E –coli and n==27 K. pneumoniae) collected from critical care unit specimen were identified tested susceptibility by Vitek 2 compact (Biomerieux India pvt. LTD.) Result: 100% of clinical isolates tested were susceptible to ertapenem. 100% of same isolates were also susceptible to imipenem. Conclusion: 100% susceptibility, suggest that ertapenem may be an alternative to other carbapenem for the treatment of infection caused by ESBL_ producing E-coli and K.pneumoniae.